Chinese justice : civil dispute resolution in contemporary China - Woo, Margaret Y. K.; Gallagher, Mary Elizabeth, 1969- (Cambridge : Cambridge University Press, 2011)
'This volume analyzes whether China's thirty years of legal reform have taken root in Chinese society by examining how ordinary citizens are using the legal system in contemporary China. It is an interdisciplinary look at law in action and at legal institutions from the bottom up, that is, beginning with those at the ground level that are using and working in the legal system. It explores the emergent Chinese conception of justice - one that seeks to balance Chinese tradition, socialist legacies, and the needs of the global market. Given the political dimension of dispute resolution in creating, settling, and changing social norms, this volume contributes to a greater understanding of political and social change in China today and of the process of legal reform generally'--
From mediatory to adjudicatory justice : the limits of civil justice reform in China / Fu Hualing and Richard Cullen -- Judicial disciplinary systems for incorrectly decided cases : the imperial Chinese heritage lives on / Carl Minzner --- Legalizing the local state : administrative'legality' at China's grassroots / Douglas B. Grob -- Economic development and the development of the legal profession in China / Randall Peerenboom -- The impact of nationalist and Maoist legacies on popular trust in legal institutions / Pierra F. Landry -- Public attitudes toward official justice in Beijing and rural China / Ethan Michelson and Benjamin L. Read -- Users and non-users : legal experience and its effect on legal consciousness / Mary E. Gallagher and Yuhua Wang -- With or without the law : the changing meaning of ordinary legal work in China, 1979-2003 / Sida Liu -- A populist threat to China's courts? / Benjamin L. Liebman -- Dispute resolution and China's grass-roots legal services / Fu Yulin -- The constitution in the courtroom : constitutional development and civil litigation in China / Thomas E. Kellogg -- Conclusion : Chinese justice from the bottom up / Margaret Y.K. Woo.
Includes bibliographical references and index.
Keywords: Justice, Administration of -- China; Dispute resolution (Law) -- China; Civil procedure -- China; Law reform -- China